Supporting the externality of intermittency in policies for renewable energy. (January 2016) - Bunn, Derek W.; Muñoz, José I.
Abstract: We analyse the joint problem of supporting renewables and resource adequacy in a liberalised electricity market and present a detailed model-based comparison of two alternative policies. We undertake this in the context of the British market. We show how, ceteris paribus,  the progressive replacement of coal with wind imposes extra costs of reserve and evaluate alternative way to meet this, whether through capacity payments funded by customers, or a reliability requirement on wind generators with capital cost or energy feed-in subsidies. We consider the reality of market concentration and the extent to which pragmatic regulation could allow prices to rise above marginal cost to reduce the extent of direct subsidies and complex market designs. We also evaluate the implied cost of carbon reduction in a progressive replacement of coal with wind, when the security is maintained by extra peaking gas. We find that support through capital allowances rather than the energy market is more efficient. Highlights: Progressively replacing coal by offshore wind may require increasing subsidies. Risk-averse investors seek higher financial hurdles with more intermittent technologies. The externality of providing extra reserves should be bundled with the renewable subsidies. Using capital grants rather than green certificates leads to lower costs.